2008
DOI: 10.1007/s00105-008-1632-x
|View full text |Cite
|
Sign up to set email alerts
|

Trombidiose des Menschen

Abstract: Trombiculiasis is an epizoonosis that occurs worldwide and is caused by various types of chiggers. Clinical findings after accidental contact with the parasitic mite larvae include erythematous papules and urticarial plaques, to some extent with vesicular transformation, which can lead to excoriations due to the intense pruritus. Prophylaxis against exposure is recommended when visiting areas known to be colonized by mites. Reactions to bites can be treated by local application of alcohol compresses or zinc lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
1
2
0
Order By: Relevance
“…They described their findings in white‐tailed deer, and their observations are consistent with the biopsies of our patient . The only report of a biopsy in humans was made by Lewerenz et al ., who also reported acanthosis and focal parakeratosis but not the presence of larvae.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…They described their findings in white‐tailed deer, and their observations are consistent with the biopsies of our patient . The only report of a biopsy in humans was made by Lewerenz et al ., who also reported acanthosis and focal parakeratosis but not the presence of larvae.…”
supporting
confidence: 90%
“…Trombidiasis presents with extremely pruritic disseminated or localized erythematous, umbilicated, firm papules with hyperkeratotic centres . However, individual hypersensitive reactions to the mites can cause different responses, from asymptomatic initial exposures to vesicles, pustules, bullae or generalized wheals . Despite displaying typical lesions, our patient presented with a previously unreported, extended presentation.…”
mentioning
confidence: 79%
“…DOI: 10.1111/jdv.12992 A three-cohort comparison with videodermatoscopic evidence of the distinct homogeneous bushy capillary microvascular pattern in psoriasis vs atopic dermatitis and contact dermatitis Editor In recent years, some studies have suggested that the diagnosis of psoriasis may be enhanced by videocapillaroscopy (VC) and videodermatoscopy (VD), non-invasive techniques able to 'in vivo' identify modifications of microvascular skin architecture. [1][2][3][4][5][6][7][8][9][10] In psoriatic lesions, low magnification obtained by standard dermatoscopy (109) shows the presence of a red-dotted pattern. Higher magnification (100-4009) by VC or VD highlights the presence of typical elongated and convoluted 'bushy' capillaries that are homogeneously distributed within the plaque.…”
mentioning
confidence: 99%